PERBANDINGAN PENGARUH CAR DAN BOPO TERHADAP ROA PADA BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH PERIODE 2016-2020 - Ragil Noviantika Silitonga; Wirman (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
The objective of this research is to compare, the effect of CAR and BOPO on ROA at Conventional Commercial Banks and Islamic Commercial Banks in 2016-2020 period. The method in this research used secondary data. Then use multiple linear regression analysis, classical assumption test, and independent sample t-test. The results of this study give, the describe that partially CAR has a positive significant effect on ROA at BNI and BRI banks during the 2016-2020 period. CAR has a partial effect, which is significant negative on ROA at BNI Syariah, and BRI Syariah during 2016-2020. While the results partially BOPO has a, negative significant effect on ROA at BNI, BRI, BNI Syariah, and BRI Syariah banks during 2016-2020. Meanwhile the results of the F, CAR and BOPO tests are significant on ROA at BNI and BRI banks, as well as at BNI syariah and BRI syariah during the 2016-2020 period. The results of the independent sample t-test indicate. Have a significant difference between the average ROA at BNI and BRI, as well as BNI syariah and BRI syariah banks between 2016 and 2020. With a higher average ROA of BNI and BRI banks